A shielded electrical cabinet
By using flame retardant fiber sponge layer, epoxy resin matrix, carbon nanotubes and magnetic iron particles to adhere to composite nanowires in the shielding layer of the electrical cabinet, the problem of insufficient electromagnetic shielding performance of the existing electrical cabinet is solved, and the Efficient, lightweight, easy to transport and install electromagnetic shielding.
Patent Information
- Application Number
- CN202411572390.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing electrical cabinets have insufficient electromagnetic shielding performance in reducing external electromagnetic radiation, and are difficult to process, heavy mass and difficult to transport commonly used materials.
A shielded electrical cabinet was designed, with a shielding layer on the peripheral wall of the cabinet body. The shielding layer consists of a flame-retardant fiber sponge layer, an epoxy resin matrix, carbon nanotubes and composite nanowires. The composite nanowires are adhered to by magnetic iron particles and Sodium alginate is modified to form.
It realizes efficient electromagnetic shielding performance, reduces weight, improves collision-proof and flame-retardant performance, and is simple in process and easy to operate on a large scale.
Smart Images

Figure CN119095365B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrical cabinet devices, and in particular to a shielded electrical cabinet. Background Art
[0002] In order to reduce the impact of external electromagnetic radiation on electronic equipment in electrical control cabinets, common methods include processing lead-based alloys into cabinets, or processing thicker steel plates into cabinets. The disadvantages are: the cabinets are difficult to form, heavy, and difficult to transport. In response to this, some companies use conventional materials to form cabinets, and then coat the inner or outer walls of the cabinets with a functional layer that has electromagnetic shielding. Common types of such functional layers include polymer-coated glass fiber, silver nanowires or other fillers, which have the advantages of easy processing and low weight. The disadvantage is that the electromagnetic shielding performance is insufficient and needs to be improved. Summary of the invention
[0003] To solve at least one of the above technical defects, the present invention provides the following technical solutions:
[0004] The present invention discloses a shielded electrical cabinet, comprising a cabinet body and a shielding layer arranged at the peripheral wall of the cabinet body, wherein the shielding layer comprises a flame-retardant fiber sponge layer and a functional layer between two flame-retardant fiber sponge layers, wherein the functional layer comprises an epoxy resin matrix and carbon nanotubes and composite nanowires distributed in the matrix. The composite nanowires are formed by attaching magnetic iron particles and modifying silver nanowires with sodium alginate.
[0005] The structure of the shielding layer is designed in the present invention, and a functional layer is formed between two flame-retardant fiber sponge layers. The functional layer is based on epoxy resin. The entire shielding layer has the advantages of light weight, windability, heat insulation, collision resistance, convenient transportation, storage and installation.
[0006] In the present invention, the silver nanowires are modified and magnetic iron particles are attached to the silver nanowires, combining the advantages of the two into one, which helps to improve the electromagnetic shielding performance. The sodium alginate modification helps to improve the dispersibility of the silver nanowires, reduce the agglomeration phenomenon in the dispersion, help to improve the uniformity of the distribution of the silver nanowires in the matrix, and also help to improve the electromagnetic shielding performance.
[0007] Further, the magnetic iron particles are attached to the silver nanowires by a coprecipitation method, and then the silver nanowires attached with the magnetic iron particles are modified by sodium alginate to form the composite nanowires;
[0008] Then, carbon nanotubes are dispersed in an epoxy resin solution and dripped into the dispersion of the composite nanowires to form a spherical composite body;
[0009] Finally, the composite body is laid between the upper and lower flame-retardant fiber sponge layers and hot-pressed to form a shielding layer.
[0010] The method of co-precipitation to make the magnetic iron particles adhere is more convenient to operate, which helps to simplify the process and control the degree of adhesion, so that the subsequent sodium alginate can better modify the silver nanowires. The carbon nanowire tubes are dispersed in the epoxy resin and drip into the composite nanowire dispersion. They are combined with the nanowires during the sphere forming process. This process makes the distribution of carbon nanotubes and nanowires more uniform. The composite is laid between the flame-retardant fiber sponge layers and hot-pressed, which is convenient for large-scale operation and has low molding difficulty.
[0011] Furthermore, the magnetic iron particles are ferroferric oxide, silver nanowires are added to ferric chloride and ferrous sulfate solutions and stirred evenly, the temperature is raised to 60-70°C and the pH is adjusted to 8-10, the temperature is raised to 80-90°C for the second time and a surfactant is added, the reaction is continued for 5-20 minutes, the solution is cooled to room temperature and the silver nanowires attached to the magnetic iron particles are magnetically selected, sodium alginate is added to the silver nanowire mixed solution attached to the magnetic iron particles and stirred for more than 10 minutes, and the solid-liquid separation is performed to obtain composite nanowires, ferroferric oxide is generated by the reaction of trivalent iron ions and divalent iron ions with hydroxide, and then precipitated and attached to the silver nanowires, the advantages of the magnetic iron particles and the silver nanowires are integrated, and the attachment of the magnetic iron particles helps to improve the electrical stability of the silver nanowires, and the sodium alginate is ionically bonded to the surface of the silver nanowires, which helps to improve the dispersibility and the uniformity of distribution in the matrix.
[0012] Furthermore, the mass ratio of the sodium alginate to the silver nanowires attached to the magnetic iron particles is 1:1-3.
[0013] Furthermore, the carbon nanotubes account for 0.01-0.05% of the mass of the epoxy resin solution, the concentration of the silver nanowire dispersion is 0.5-3 mg / ml, and the modified silver nanowires can meet the high electromagnetic shielding requirements of the subsequent shielding layer under low concentration dispersion.
[0014] Furthermore, polyetherimide and polyurethane are mixed in a solvent, heated to 55-70°C and stirred for more than 10 hours, and then isocyanate is added for cross-linking reaction for 0.4-2 hours to obtain a spinning solution, and the spinning solution is formed into a layered sponge, i.e., a flame-retardant fiber sponge layer, by a spinning device. Polyetherimide is an aromatic polymer with the advantages of high temperature resistance and good mechanical properties. Polyurethane has excellent tensile resilience. The fiber sponge is obtained by spinning under isocyanate cross-linking, and has excellent flame retardancy, heat insulation, and stretch elasticity.
[0015] Furthermore, it also includes a waterproof film layer. The waterproof film layer is arranged on the flame-retardant fiber sponge layer to reduce the absorption of water by the fiber sponge layer. The waterproof film layer is made of polyvinyl chloride, polypropylene and the like.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] 1. The present invention designs the composition of the shielding layer. Under the modification of sodium alginate and the attachment of magnetic iron particles, the dispersibility of the composite nanowires is improved, and the high electromagnetic shielding performance of the shielding layer can be maintained while reducing the dosage. The flame-retardant fiber sponge layer above and below the functional layer helps to reduce weight and improve anti-collision, flame retardancy and other properties. The molded shielding layer is light and can be wound, which is convenient for transportation and installation. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 is the SEM image of the composite nanowires in Example 1. DETAILED DESCRIPTION
[0020] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0021] Example 1
[0022] A shielded electrical cabinet includes a cabinet body and a shielding layer installed on the peripheral wall of the cabinet body, wherein the shielding layer structure includes: a flame retardant fiber sponge layer / a functional layer / a flame retardant fiber sponge layer, and the shielding layer is prepared as follows:
[0023] Preparation of flame retardant fiber sponge layer:
[0024] Polyetherimide (PEI-1000) and polyurethane (PU-4394) were placed in a solvent at a mass ratio of 3:1 and stirred at 50°C for 10 hours to form a solution (18wt%). The solvent was composed of N,N-dimethylformamide and N-methylpyrrolidone at a volume ratio of 2:1. A crosslinking agent, isocyanate, was added to the solution and stirred for 2 hours to form a spinning solution. The isocyanate was 3% of the total amount of polyetherimide and polyurethane. The flame-retardant fiber sponge layer was prepared by spinning at a relative humidity of 80% with a volume density of 16 mg / cm 3 , porosity 95% and thickness 1.5mm.
[0025] Preparation of functional layer:
[0026] The functional layer comprises an epoxy resin matrix, and carbon nanotubes and composite nanowires distributed in the matrix. The composite nanowires are formed by attaching magnetic iron particles and modifying silver nanowires with sodium alginate.
[0027] Preparation of composite nanowires:
[0028] The magnetic iron particles are attached to the silver nanowires by a coprecipitation method. Specifically, the magnetic iron particles are ferroferric oxide. According to the mass ratio of ferroferric oxide to silver nanowires of 0.2:1, corresponding molar amounts of ferric chloride hexahydrate and ferrous sulfate heptahydrate are added. The silver nanowires are added to the ferric chloride and ferrous sulfate solution (1.5 mg / ml) and stirred evenly. After heating to 65°C, the pH is adjusted to 9 with sodium hydroxide. The temperature is raised to 85°C for the second time and a surfactant (SDS) is added. The reaction is continued for 15 minutes. The silver nanowires attached to the magnetic iron particles are selected by magnetic absorption, washed with anhydrous ethanol and added to deionized water (1.5 mg / ml). Sodium alginate is added to the mixed solution of the silver nanowires attached to the magnetic iron particles and stirred for more than 10 minutes. The mass ratio of sodium alginate to the silver nanowires attached to the magnetic iron particles is 1:2. The composite nanowires are obtained by filtration. The SEM image of the composite nanowires is shown in FIG. Figure 1 As shown, it can be seen that the magnetic iron particles are dispersedly attached to the silver nanowires.
[0029] Dissolve bisphenol A epoxy resin in acetone solvent, add 0.02% of carboxylated carbon nanotubes (aspect ratio of 90-100) based on the mass of bisphenol A epoxy resin, 0.02% of polyethylene glycol octylphenyl ether based on the mass of bisphenol A epoxy resin, and 10% of modified imidazole latent curing agent based on the mass of bisphenol A epoxy resin, stir for 20 minutes, and ultrasonically disperse for 2 hours for standby use.
[0030] A polyvinyl pyrrolidone dispersant accounting for 3.5% of the mass of bisphenol A epoxy resin is dissolved in deionized water to form a 0.003g / ml solution, and then the composite silver nanowires are added to the solution to form a 2mg / ml mixed solution, the mixed solution is placed in a container and stirred, and the prepared bisphenol A epoxy resin solution is dropped into the stirred mixed solution, the formed spheres are filtered out, repeatedly washed and dried, and the obtained spheres are carbon nanotube / silver nanowire spherical composites with a particle size of 100-200μm.
[0031] The composite body is laid between the upper and lower flame-retardant fiber sponge layers and hot-pressed to form a shielding layer, the thickness of which is 4.6 mm.
[0032] Example 2
[0033] A shielded electrical cabinet includes a cabinet body and a shielding layer installed on the peripheral wall of the cabinet body, wherein the shielding layer structure includes: a flame retardant fiber sponge layer / a functional layer / a flame retardant fiber sponge layer, and the shielding layer is prepared as follows:
[0034] Preparation of flame retardant fiber sponge layer:
[0035] Polyetherimide (PEI-1000) and polyurethane (PU-4394) were placed in a solvent at a mass ratio of 3.2:1 and stirred at 55°C for 12 hours to form a solution (20wt%). The solvent was composed of N,N-dimethylformamide and N-methylpyrrolidone in a volume ratio of 1:1. A crosslinking agent, isocyanate, was added to the solution and stirred for 2 hours to form a spinning solution. The isocyanate was 2.5% of the total amount of polyetherimide and polyurethane. The flame-retardant fiber sponge layer was prepared by spinning at a relative humidity of 80% with a volume density of 15 mg / cm 3 , porosity 90% and thickness 1.5mm.
[0036] Preparation of functional layer:
[0037] The functional layer comprises an epoxy resin matrix, and carbon nanotubes and composite nanowires distributed in the matrix. The composite nanowires are formed by attaching magnetic iron particles and modifying silver nanowires with sodium alginate.
[0038] Preparation of composite nanowires:
[0039] The magnetic iron particles are attached to the silver nanowires by a coprecipitation method. Specifically, the magnetic iron particles are ferroferric oxide. According to the mass ratio of ferroferric oxide to silver nanowires of 0.25:1, corresponding molar amounts of ferric chloride hexahydrate and ferrous sulfate heptahydrate are added. The silver nanowires are added to the ferric chloride and ferrous sulfate solutions (2 mg / ml) and stirred evenly. After heating to 70°C, the pH value is adjusted to 9 with sodium hydroxide. The temperature is heated to 90°C for the second time and a surfactant (SDS) is added. The reaction is continued for 10 minutes. The silver nanowires attached to the magnetic iron particles are selected by magnetic attraction, washed with anhydrous ethanol and added to deionized water (2 mg / ml). Sodium alginate is added to the mixed solution of the silver nanowires attached to the magnetic iron particles and stirred for more than 10 minutes. The mass ratio of sodium alginate to the silver nanowires attached to the magnetic iron particles is 1:3. The composite nanowires are obtained by filtration.
[0040] Dissolve bisphenol A epoxy resin in acetone solvent, add 0.02% of carboxylated carbon nanotubes (aspect ratio of 90-100) based on the mass of bisphenol A epoxy resin, 0.02% of polyethylene glycol octylphenyl ether based on the mass of bisphenol A epoxy resin, and 10% of modified imidazole latent curing agent based on the mass of bisphenol A epoxy resin, stir for 20 minutes, and ultrasonically disperse for 2 hours for standby use.
[0041] A polyvinyl pyrrolidone dispersant accounting for 3.0% of the mass of bisphenol A epoxy resin is dissolved in deionized water to form a 0.004g / ml solution, and then the composite silver nanowires are added to the solution to form a 2mg / ml mixed solution, the mixed solution is placed in a container and stirred, and the prepared bisphenol A epoxy resin solution is dropped into the stirred mixed solution, the formed spheres are filtered out, repeatedly washed and dried, and the obtained spheres are carbon nanotube / silver nanowire spherical composites with a particle size of 100-200μm.
[0042] The composite body is laid between the upper and lower flame-retardant fiber sponge layers and hot-pressed to form a shielding layer, the thickness of which is 4.6 mm.
[0043] Example 3
[0044] A shielded electrical cabinet includes a cabinet body and a shielding layer installed on the peripheral wall of the cabinet body, wherein the shielding layer structure includes: a flame retardant fiber sponge layer / a functional layer / a flame retardant fiber sponge layer, and the shielding layer is prepared as follows:
[0045] Preparation of flame retardant fiber sponge layer:
[0046] Polyetherimide (PEI-1000) and polyurethane (PU-4394) were placed in a solvent at a mass ratio of 4:1 and stirred at 60°C for 8 hours to form a solution (16wt%). The solvent was composed of N,N-dimethylformamide and N-methylpyrrolidone in a volume ratio of 1:1. A crosslinking agent, isocyanate, was added to the solution and stirred for 2 hours to form a spinning solution. The isocyanate was 2% of the total amount of polyetherimide and polyurethane. The flame-retardant fiber sponge layer was prepared by spinning at a relative humidity of 80% with a volume density of 12mg / cm 3 , porosity 98% and thickness 1.5mm.
[0047] Preparation of functional layer:
[0048] The functional layer comprises an epoxy resin matrix, carbon nanotubes and composite nanowires distributed in the matrix, and the composite nanowires are formed by attaching magnetic iron particles and modifying silver nanowires with sodium alginate.
[0049] Preparation of composite nanowires:
[0050] The magnetic iron particles are attached to the silver nanowires by a coprecipitation method. Specifically, the magnetic iron particles are ferroferric oxide. According to the mass ratio of ferroferric oxide to silver nanowires of 0.15:1, corresponding molar amounts of ferric chloride hexahydrate and ferrous sulfate heptahydrate are added. The silver nanowires are added to a solution of ferric chloride and ferrous sulfate (1 mg / ml) and stirred evenly. After heating to 60°C, the pH value is adjusted to 9 with sodium hydroxide. The temperature is heated to 80°C for the second time and a surfactant (SDS) is added. The reaction is continued for 20 minutes. The silver nanowires attached to the magnetic iron particles are selected by magnetic attraction, washed with anhydrous ethanol and added to deionized water (1.5 mg / ml). Sodium alginate is added to the mixed solution of the silver nanowires attached to the magnetic iron particles and stirred for reaction for more than 10 minutes. The mass ratio of sodium alginate to the silver nanowires attached to the magnetic iron particles is 1:1.8. The composite nanowires are obtained by filtration.
[0051] Dissolve bisphenol A epoxy resin in acetone solvent, add 0.02% of carboxylated carbon nanotubes (aspect ratio of 90-100) based on the mass of bisphenol A epoxy resin, 0.02% of polyethylene glycol octylphenyl ether based on the mass of bisphenol A epoxy resin, and 10% of modified imidazole latent curing agent based on the mass of bisphenol A epoxy resin, stir for 20 minutes, and ultrasonically disperse for 2 hours for standby use.
[0052] A polyvinyl pyrrolidone dispersant accounting for 3.5% of the mass of bisphenol A epoxy resin is dissolved in deionized water to form a 0.003g / ml solution, and then the composite silver nanowires are added to the solution to form a 2mg / ml mixed solution, the mixed solution is placed in a container and stirred, and the prepared bisphenol A epoxy resin solution is dropped into the stirred mixed solution, the formed spheres are filtered out, repeatedly washed and dried, and the obtained spheres are carbon nanotube / silver nanowire spherical composites with a particle size of 100-200μm.
[0053] The composite body is laid between the upper and lower flame-retardant fiber sponge layers and hot-pressed to form a shielding layer, the thickness of which is 4.6 mm.
[0054] Comparative Example 1
[0055] Compared with Example 3, this example does not involve the step of precipitating and attaching ferroferric oxide on the silver nanowires, and the silver nanowires are only modified with sodium alginate.
[0056] Comparative Example 2
[0057] Compared with Example 3, in this example, there is no precipitation and attachment process of ferroferric oxide on the silver nanowires. After the spherical composite body is mixed with ferroferric oxide, it is laid between the upper and lower flame-retardant fiber sponge layers.
[0058] The electromagnetic shielding effectiveness of the shielding layer prepared above was tested in a frequency range of 12 to 18 GHz, as shown in Table 1:
[0059] Table 1
[0060]
[0061] It can be seen that after the magnetic iron particles are combined with silver nanowires and modified with sodium alginate, the properties of silver reflecting and absorbing electromagnetic waves are combined with the properties of magnetic influence and absorption of electromagnetic waves, and the high dispersion of the composite nanowires synergistically improves the electromagnetic shielding performance. At a low concentration of the composite nanowire dispersion, the subsequently prepared shielding layer can also have high electromagnetic shielding performance.
[0062] The above are only preferred embodiments of the present invention. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A shielded electrical cabinet, comprising a cabinet body and a shielding layer arranged on the peripheral wall of the cabinet body, characterized in that: The shielding layer includes a flame retardant fiber sponge layer and a functional layer between the two flame retardant fiber sponge layers, wherein the functional layer includes an epoxy resin matrix and carbon nanotubes and composite nanowires distributed in the matrix; wherein the composite nanowires are formed by attaching magnetic iron particles and modifying silver nanowires with sodium alginate; The magnetic iron particles are attached to the silver nanowires by a coprecipitation method, and then the silver nanowires attached with the magnetic iron particles are modified by sodium alginate to form the composite nanowires; Dispersing carbon nanotubes in an epoxy resin solution and dripping the solution into the dispersion of the composite nanowires to form a spherical composite; The composite body is laid between the upper and lower flame-retardant fiber sponge layers and hot-pressed to form a shielding layer.
2. A shielded electrical cabinet as claimed in claim 1, characterized in that: The magnetic iron particles are ferroferric oxide. Silver nanowires are added to ferric chloride and ferrous sulfate solutions and stirred evenly. The temperature is raised to 60-70° C. and the pH is adjusted to 8-10. The temperature is raised to 80-90° C. for a second time and a surfactant is added. The reaction is continued for 5-20 minutes. The mixture is cooled to room temperature and the silver nanowires attached to the magnetic iron particles are magnetically selected. Sodium alginate is added to the silver nanowire mixed solution attached to the magnetic iron particles and stirred for reaction for more than 10 minutes. The solid-liquid separation is performed to obtain the composite nanowires.
3. A shielded electrical cabinet as claimed in claim 2, characterized in that: The mass ratio of the sodium alginate to the silver nanowires attached to the magnetic iron particles is 1:1-3.
4. A shielded electrical cabinet as claimed in claim 1, characterized in that: The carbon nanotubes account for 0.01-0.05% of the mass of the epoxy resin solution, and the dispersion concentration of the composite nanowires is 0.5-3 mg / ml.
5. A shielded electrical cabinet as claimed in claim 1, characterized in that: The polyetherimide and polyurethane are mixed in a solvent, heated to 55-70° C. and stirred for more than 10 hours, and then isocyanate is added for cross-linking reaction for 0.4-2 hours to obtain a spinning solution, and the spinning solution is formed into a layered sponge body through a spinning device to obtain the flame-retardant fiber sponge layer.
6. A shielded electrical cabinet as claimed in claim 1, characterized in that: It also includes a waterproof membrane layer, which is arranged on the flame-retardant fiber sponge layer.
Citation Information
Patent Citations
Cooperated enhanced electromagnetic shielding film and preparation method thereof
CN110294857A
Magnetoelectric coupling type electromagnetic shielding film and preparation method and application
CN113831599A